Longitudinal assessment of SARS-CoV-2 nucleocapsid antigenemia in patients hospitalized with COVID-19. (28th October 2021) - Verkerke, Hans; Harrington, Kristin; McLendon, Kaleb; O'Sick, William; Potlapalli, Sindhu; Shin, Sooncheon; Allen, Jerry William Lynn; Horwath, Michael; Arthur, Connie; Rha, Jennifer
Abstract: While RT-PCR tests of nasopharyngeal swabs remain the gold standard for the detection of SARS-CoV-2 infection and monitoring of COVID-19 disease progression, measurement of nucleocapsid antigenemia in serum and plasma samples is an underexplored alternative proxy for disease severity. To explore the dynamics of nucleocapsid antigenemia, we measured levels of nucleocapsid antigen using a highly sensitive Single Molecule Array (Simoa) assay in 817 serially collected serum and plasma samples from 93 PCR-confirmed COVID-19 patients for whom symptom onset date could be extracted by chart review. In a subset of these individuals (n=13), we measured seroconversion by titering for receptor binding domain (RBD) specific IgG, IgA, and IgM. A model of exponential decay was fit to data from individuals with high resolution daily sampling (N=34), from which the half-life of SARS-CoV-2 nucleocapsid in serum was determined. Mean nucleocapsid half-life in this group of patients was 1.17 days (SD=0.82). Nucleocapsid levels were significantly higher in the first 10 days following symptom onset in patients who died compared to those with a milder disease course (p=0.004). Further, mortality was associated with a trend toward longer nucleocapsid half-life (1.51 days vs. 0.79 days) (p=0.10). In patients who had both antibody and antigenemia data available, antibody response was temporally linked to antigen decay, reaching peak levels as antigen was cleared from the blood. Our data identify SARS-CoV-2 nucleocapsid antigenemia as a potential diagnostic tool for acute COVID-19 disease and an early biomarker associated with disease severity.